Perbedaan Self Assessment dan Peer Assessment Terhadap Kompetensi Pemasangan Infus Ditinjau dari Motivasi - Aan Devianto; AA. Soebiyanto; Hari Wujoso (Journal of Health (JoH), 2014)
Background: There are different assessment methods that aim to evaluate the learning process of students, such as formative or summative methods. The assessment methods that are still rarely used in nursing education are self-assessment and peer assessment. Therefore, in order to determine whether these methods have advantages or disadvantages, investigation is needed. The research that is conducted with these methods is a research on the competencies on infusion installment that is also assessed from the students’ motivation to follow the learning process. Subjects and Methods : This research is a quantitative research using true experimental approach. The population is the students. The samples are obtained by using random sampling. The independent variables in this study are a self -assessment, peer assessment and motivation, while the dependent variable is the infusion installment competency. There are three purposes of this study. The first is to analyze the differences in self-assessment and peer-assessment of infusion installment competence. The second is to analyze the differences of motivation on infusion installment competence. The last is to analyze the interaction between the assessment of the competence models and the level of motivation on infusion installment. Two-path analysis of variance (ANOVA) was used to test statistical data. Results: The results showed that there were significant differences between self-assessment and peer-assessment of competence on infusion installment with the results of p= 0.000. Other results also showed a significant difference between high motivation and low motivation on infusion installment competence with the results of p= 0.002. In addition to that, the statistical test also showed the interaction between the models of the assessment and the motivation on infusion installment competence with p = 0.000. Additionally, there are also some treatment groups that were not significant with p= scores > 0.05.